Investigation of Consumer Insights and Development of Alternative Protein-Rich Products from Alcoholic Beverage Byproducts - Nguyen, Minh Quan; Nguyen, Thi Thao; Nguyen, Tien Cuong (Engineering and Technology For Sustainable Development, 2024)
The research aims to promote the transformation of the food system in Vietnam toward sustainable, healthy diets by investigating consumer choices and perceptions regarding alternative protein products and developing a product utilizing alcoholic beverage byproducts. This study consisted of (i) the investigation of consumer knowledge of alternative protein and their attitude about alternative protein products, (ii) the proposition of a production process for protein powder derived from spent yeast, and (iii) the formulation of energy bars using alternative protein. A survey of 260 young people was conducted to gather information on their knowledge of alternative proteins and their desires for a novel energy bar. The spent yeast was hydrolyzed with 1% ethanol (v/w) and the enzyme Alcalase (1% w/w) for 24 hours to achieve a high level of efficiency in protein recovery (84.9%). A novel energy bar was created with alternative protein sources derived from 13.57 g Brewer’s Spent Yeast (BSY) protein and 10.9 g Distiller’s Dried Grains with Soluble (DDGS) protein, resulting in a product with substantial energy (252.85 kcal/serving) and a significant protein content (14.9 g/serving). The product exhibits a notable energy density of 3.89 Kcal per gram, low Glycemic Index (GI) carbohydrate from oats, unsaturated fat from peanut butter, healthy sweeteners from malt syrup, and a high protein content.